Mass Extinction on Noah’s Ark - Żółkoś, Monika (Porównania, 2021)
The paper presents an ecocritical interpretation of the contemporary version of biblical flood myth in Julian Barnes’ novel A History of the World in 10½ chapters. The article analyses the first chapter of the noel, The Stowaway, where the biblical events are presented from the perspective of animal character. It brings the subject of animal narration and narrative strategies to challenge the anthropocentrism of language. An important issue in the paper is the key problem of Animal Studies – the act of naming “the animal” and discoursive ways of categorizing the “nature”. In the perspective of environmental criticism, the biblical flood transforms into a history of ecocide and mass extinction.